El dorado - Oldfield, Jenny (Hodder Children's London, 2001)
Staying with friends by Squaw Lake, Kristie and Lisa observe their first herd of wild mustangs, led by magnificent black stallion, El Dorado. When the stallion vanishes and a ranch foal is found battered, the finger of suspicion points at El Dorado